Lateral solids meso-mixing in pseudo-2D fluidized beds by means of TFM simulations - Hernández- Jiménez, Fernando; Sánchez-Prieto, Javier; Cano-Pleite, Eduardo; Soria-Verdugo, Antonio (Powder Technology, 2018)
This work studies the solids mixing process in fluidized beds by means of numerical simulations using the two-fluid model (TFM) available in the MFIX code. The numerical results are compared with experiments conducted in a pseudo-2D fluidized bed. The experiments were performed by placing particles of the same diameter and density but of different colour in two vertical layers. To reproduce numerically the experimental results, three phases are defined: one for the gas phase and two for the solid phases, corresponding to the particles of different colours employed in the experiments, to make them separately traceable. To improve the simulation prediction, a friction model that accounts for the effect of the front and rear walls on the continuum solid phases was introduced in the TFM. Mixing times of the same order of magnitude are obtained from the simulations and the experiments when the mixing process is analysed macroscopically. Furthermore, the simulations are employed to study the solids mixing in the fluidized bed based on a more detailed mixing index. This new mixing index is determined from information of the three phases involved and it is used to predict the mixing behaviours beyond the capabilities of the experimental facility.
Keywords: fluidized bed; solids mixing; mixing index; TFM; pseudo-2D; wall friction; JCR; Scopus